Real Life Population Pharmacokinetics Modelling of Eight Factors VIII in Patients with Severe Haemophilia A: Is It Always Relevant to Switch to an Extended Half-Life? - Quentin Allard; Zoubir Djerada; Claire Pouplard; Yohann Repessé; Dominique Desprez; Hubert Galinat; Birgit Frotscher; Claire Berger; Annie Harroche; Anne Ryman; Claire Flaujac; Pierre Chamouni; et al. (MDPI AG, 2020)
We retrospectively analysed the data files of 171 adults and 87 children/adolescents with severe haemophilia, except for 14 patients (moderate; minor) (1), to develop a global population pharmacokinetic (PK) model for eight factors VIII (FVIII) that could estimate individual PK parameters for targeting the desired level of FVIII activity (FVIII:C); and (2) to compare half-life (HL) in patients switching from a standard half-life (SHL) to an extended half-life (EHL) and evaluate the relevance of the switch. One-stage clotting assay for the measurement of FVIII activity (FVIII:C, IU/mL) was used for population PK modelling. The software, Monolix version 2019R1, was used for non-linear mixed-effects modelling. A linear two-compartment model best described FVIII:C. The estimated PK parameters (between-subject variability) were: 2640 mL (23.2%) for volume of central compartment (V1), 339 mL (46.8%) for volume of peripheral compartment (V2), 135 mL/h for Q (fixed random effect), and 204 mL/h (34.9%) for clearance (Cl). Weight, age, and categorical covariate EHL were found to influence Cl and only weight for V1. This model can be used for all of the FVIII cited in the study. Moreover, we demonstrated, in accordance with previous studies, that Elocta had longer half-life (EHL) than SHL (mean ratio: 1.48) as compared to Advate, Factane, Kogenate, Novoeight, and Refacto.